Sistema de control para el suministro de heparina. - Ochoa, Humberto; Reyna, Javier; Ramos, Jesús; Mendoza, Genaro; Villa, Edgar; Quiñones, Maximiliano (Revista Mexicana de Ingeniería Biomédica, 2006)
This article presents the characterization of a system which controls the flow rate of heparin. The system handles up to eight different syringes and is able to control twelve different flow rates for each syringe, as well as the application of a bole. A microcontroller accepts command codes of syringe type and flow rate through its slave port. The codes can be sent into the system using the parallel port of a computer, the port of a microcontroller configured as master, or mini switches. Results show that the system is quite exact and can be used to operate on a bloodline circuit during a hemodialysis session without any risk.